A systemic transcriptome analysis reveals the regulation of neural stem cell maintenance by an E2F1-miRNA feedback loop - Palm, Thomas; Hemmer, Kathrin; Winter, Julia; Fricke, Inga B.; Tarbashevich, Katsiaryna; Sadeghi Shakib, Fereshteh; Rudolph, Ina-Maria; Hillje, Anna-Lena; De Luca, Paola; Bahnassawy, Lamia'a; Madel, Rabea; Viel, Thomas; et al. (Nucleic acids research, 2013)
Stem cell fate decisions are controlled by a molecular network in which transcription factors and miRNAs are of key importance. To systemically investigate their impact on neural stem cell (NSC) maintenance and neuronal commitment, we performed a high-throughput mRNA and miRNA profiling and isolated functional interaction networks of involved mechanisms. Thereby, we identified an E2F1-miRNA feedback loop as important regulator of NSC fate decisions. Although E2F1 supports NSC proliferation and represses transcription of miRNAs from the miR-17∼92 and miR-106a∼363 clusters, these miRNAs are transiently up-regulated at early stages of neuronal differentiation. In these early committed cells, increased miRNAs expression levels directly repress E2F1 mRNA levels and inhibit cellular proliferation. In mice, we demonstrated that these miRNAs are expressed in the neurogenic areas and that E2F1 inhibition represses NSC proliferation. The here presented data suggest a novel interaction mechanism between E2F1 and miR-17∼92 / miR-106a∼363 miRNAs in controlling NSC proliferation and neuronal differentiation.